THE EFFECT OF SELF-COMPASSION ON DEPRESSION AMONG UNIVERSITY STUDENTS IN YOGYAKARTA - Nashori, Fuad; Saputri D, Leonita Ikasari; Lubis, Nurul Siti Jauhara (Psychosophia: Journal of Psychology, Religion, and Humanity, 2024)
The phenomenon of low mental health among Indonesian university students is of concern to experts, professionals, and the public. The high prevalence of depression around university students is an indication of this. The present study aims to determine the effect of self-compassion on depression among university students in Special Region of Yogyakarta. The study involved 280 individuals who were registered as active students at universities in Yogyakarta. The Self-Compassion Scale and the DASS-42 depression subscale were employed as the measurements. The data analysis techniques used were product moment and regression analysis. The objective of product moment is to discover how self-compassion affects depression in university students. Regression analysis is used to analyze the respective contributions of each component of self-compassion to depression in university students. The proposed hypothesis is that there is influence self-compassion towards students’ depression and the contribution of each aspect of self-compassion to students’ depression.